Double synchronous primary gastric and thyroid cancer - Almasood, Abdulhakeem; Hussain, Mohammed; Aljabali, Mohammed; Ali, Bandar Idrees (International Surgery Journal, 2020)
Second or multiple primary malignancies is very rare and the number of patients diagnosed with multiple primary cancers has recently been increasing due to the improved diagnostic techniques. Herein we report a very rare case of synchronous double primary cancer of the stomach and thyroid gland for the 39 years old lady who presented with a short period of abdominal pain were diagnosed to have an invasive adenocarcinoma with signet ring differentiation of the stomach by gastroscopy and biopsy. Computed tomography and positron emission tomography scan showed high fludeoxyglucose uptake of the thyroid gland were biopsied to confirm the malignancy. underwent initially for radical distal gastrectomy followed by adjuvant chemotherapy and interval total thyroidectomy. Although Synchronous tumors are defined as ≥2 primary tumors occurring within 6 months of diagnosis of the first primary tumor, our case was discovered concomitantly at the first presentation of the patient. The prognosis of patients with multiple primary cancers can be determined independently by the stage of each cancer.